PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Evi Yuniarsi; Johanes Sapri (UNIB Press, 2022)
This research aims to describe application of the Problem Based Learning (PBL) model which can improve the critical thinking and the learning achievement. The method used in the types of research carried out were Classroom Action Research (CAR) and quasi-experiments . The subjects of this research were students of class VIII SMP Negeri 2 Merapi Barat in semester 2 of the 2020/ 2021 academic year. The number of students for the CAR class is 32 people, for the Experiment class 31 people, and for the Control class 30 people. The data collection method in this research used the Problem Based Learning (PBL) model observation sheet, observation sheet on students' critical thinking and learning outcomes tests. The data analysis used an average score and a test which consisted of a different test between cycles and a two-sample difference test that was not related. The results showed that the application of the Problem Based Learning (PBL) model could improve critical thinking, learning achievement and the effectiveness of student learning outcomes in Indonesian class VIII SMP Negeri 2 Merapi Barat